Poop Feminism – Fäkalkomik als weibliche Selbstermächtigung - Balke, Gregor (transcript, 2020)
Poop Feminism describes fecal comedy as a new form of female self-empowerment that is becoming increasingly visible in the resonating space of contemporary popular culture.